Energy and Exergy Analysis of Rumaila-Basra Gas Turbine Power Plant During Hot Season - Faisal, Safaa Hameed; Al.Mudhaffar, Mujtaba; Khetar, Ali Disher (Basrah Journal for Engineering Sciences, 2017)
In this paper, energy and exergy concepts have been carried out on one of the largest gas turbine power plants in Iraq (Rumaila-Basra). Both ISO operating conditions as well as actual operating data recorded for one month in hot season are considered. Results indicate that a lot of heat energy accompanied with remarkable exergy is discharged to the atmosphere. Also, it is found that the combustion chamber has the largest exergy destruction among the plant components. Possibility of cooling the intake air drawn by the compressor and its effects on the plant performance is studied. The required cooling load is found to be in the range 3379 T.R for part load operation to 4723.3 T.R for full load operation.